The Development of The Self-Management Program for Diabetes mellitus patients with third stage Chronic Kidney Disease - จันทชาติ อัมพร; มีแป้น มาลี; จาบประไพ เพ็ญศรี (Journal of Preventive Medicine Association of Thailand, 2018)
This research and development study aimed to develop nursing model for the third stage of chronic kidney disease patients using by self-management concept. Two sample groups are 13 multidisciplinary teams and 57 diabetic patients with stage 3 chronic kidney disease. Experimental tool is a manual of chronic kidney disease education and self-care to slow down kidney degeneration. The data collection tool was an open-ended questionnaire designed to study the chronic kidney disease care situation. Data recordings, issues and barriers from medical records, Clinical Indicator Format, Knowledge Assessment Model for Chronic Kidney Patients, self-management behavior for diabetic patients and hypertension and satisfaction questionnaire of professional nurses and multidisciplinary team. Examined by 3 experts and tests for reliability were 0.80, 0.83, and 0.89 respectively. Qualitative analysis is done by content analysis, general information uses descriptive statistics, compare the difference in average knowledge scores, self-management behavior of chronic kidney patients and clinical indicators before and after the use of paired t-tests and Wilcoxon signed-ranks test at .05 significance level. The results of the study revealed that the mean score of knowledge after using the third stage chronic kidney disease model was higher than before the experiment. Mean scores of self-management behaviors before and after the use of the third-stage chronic kidney disease nursing model as a whole and at the individual level were significantly different at the .05 level. Clinical indicators include fasting blood sugar, HbA1c level, creatinine level and Glomerular filtration rate. There were statistically significant differences at .05 level. The systolic and diastolic blood pressure, BMI are not different. Multidisciplinary team has satisfaction level at high level.